COVID-19 Pneumonia Mimicking Immunotherapy-Induced Pneumonitis on 18F-FDG PET/CT in a Patient Under Treatment With Nivolumab. (August 2020) - Artigas, Carlos; Lemort, Marc; Mestrez, Fabienne; Gil, Thierry; Flamen, Patrick
Abstract : Abstract: Within a few months, coronavirus disease 2019 (COVID-19) has become a pandemic with more than 2 million patients infected and a high mortality rate. Early detection of COVID-19 in oncologic patients is crucial in order to rapidly apply isolation measures and avoid nosocomial spread. However, early diagnosis may be challenging, especially in cancer patients under treatment with immunotherapy as drug-induced pneumonitis can present similar clinical and radiological features. We describe the findings of a SARS-CoV-2 infection on PET/CT with 18 F-FDG in a 51-year-old man with metastatic renal cell carcinoma under treatment with nivolumab.